Signaling Crosstalk between PPARγ and BMP2 in Mesenchymal Stem Cells - Ichiro Takada; Yoshiko Yogiashi; Shigeaki Kato (PPAR Research)
Recent studies have revealed that PPARγ’s transactivation function is regulated by extracellular signals. In particular, cytokines and Wnt family proteins suppress the ligand-inducible transactivation function of PPARγ and attenuate adipogenesis/osteoblastogenesis switching in mesenchymal stem cells (MSCs). For example, Wnt5a suppresses PPARγ transcriptional activity through the NLK/SETDB1/CHD7 pathway. Among these factors, BMP2 strongly induces bone formation, but the effect of BMP2 on PPARγ function remains unclear. We examined the effect of BMP2 and PPARγ in ST2 cells and found that PPARγ activation affected BMP2’s signaling pathway through epigenetic regulation. Although BMP2 did not interfere with PPARγ-mediated adipogenesis, BMP2 increased mRNA expression levels of PPARγ target genes (such as Fabp4 and Nr1h3) when cells were first treated with troglitazone (TRO). Moreover, PPARγ activation affected BMP2 through enhancement of histone activation markers (acetylated histone H3 and trimethylated Lys4 of histone H3) on the Runx2 promoter. After TRO treatment for three hours, BMP2 enhanced the levels of active histone marks on the promoter of a PPARγ target gene. These results suggest that the order of treatment with BMP2 and a PPARγ ligand is critical for adipogenesis and osteoblastogenesis switching in MSCs.